2018
DOI: 10.26508/lsa.201800070
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and C9orf72 neuropathology identify ribosomes as poly-GR/PR interactors driving toxicity

Abstract: Proteomics and neuropathological validation show that aberrant poly-GR/PR proteins in C9orf72 ALS/FTD bind STAU2 and ribosomes and inhibit translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
115
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 44 publications
29
115
0
Order By: Relevance
“…One was that the Arg appears to mediate promiscuous binding to the proteome and the second was that these interactions are responsible for mitigating toxicity. The Arg-rich DPRs in particular enriched for proteins involved in ribosome biogenesis and RNA splicing machinery, which is consistent with prior findings (17,(34)(35)(36). However, we also found additional novel interactions with proteins involved in ribosome-translation, cytoskeleton and chromatin machineries (Fig 2B).…”
Section: Resultssupporting
confidence: 91%
“…One was that the Arg appears to mediate promiscuous binding to the proteome and the second was that these interactions are responsible for mitigating toxicity. The Arg-rich DPRs in particular enriched for proteins involved in ribosome biogenesis and RNA splicing machinery, which is consistent with prior findings (17,(34)(35)(36). However, we also found additional novel interactions with proteins involved in ribosome-translation, cytoskeleton and chromatin machineries (Fig 2B).…”
Section: Resultssupporting
confidence: 91%
“…We next measured the basal rate of protein synthesis in C9 patient and control iPSC-derived MNs and at the same time asked whether ETF1 could in fact regulate this process in human neurons. ALS-C9 patient MNs exhibited significantly reduced levels of de novo protein synthesis relative to control MNs in accordance with previous reports 17, [54][55][56] (day 50, n=2 patients vs 1 control, n=3 independent biological replicates; siSCR control vs siSCR C9: p < 0.0001, 44% decrease ± 4) ( Supplementary Fig. 6f).…”
Section: Etf1 Mediates a Shift From Protein Translation To Mrna Degrasupporting
confidence: 91%
“…We observed upregulation of many genes involved in ribosome biogenesis and assembly. This is of interest in view of recent interactome studies and yeast genetic modifier screens that show toxic di‐peptide repeat proteins play a role in ribosomal processing/biogenesis and reduce overall cell translation (Chai & Gitler, ; Hartmann et al, ). These studies thus provide indirect support for astrocyte DPRs having a role in the observed dysregulation of ribosomal processing genes.…”
Section: Discussionmentioning
confidence: 99%